RESPON REMAJA TERHADAP METODA EDUTAINMENT: HIV/AIDS Dan NARKOBA Di WILAYAH BERESIKO TINGGI PENULARAN Dan PENYALAHGUNAAN NARKOBA - Martina, Siska Evi; Redjeki, Gerardina Sri (Jurnal Ilmiah Keperawatan, 2020)
Health promotion on HIV/AIDS and drugs for adolescent is an important project. The project activites should be that innovative and adolescents according to their interests. This study aimed to identify the response of adolescents on health promotion about HIV / AIDS and drugs through edutainment in high risk environment transmission drugs abuse and HIV, Jakarta. This study was a quasi-experiment is a game of snakes and ladders which contains information on HIV and drugs. By using the calculation G-power version 3.1.9.2 with effect size of 0.5, a error probability of 0.05 and 0.08 power size, found the number of a sample of 102 respondents. But the implementation of the study obtained a sample of 148 respondents. This is due to interest teenagers to follow edutainment on HIV / AIDS and Drugs. The sampling technique in this research is accidental sampling, to determine 4 (four) district as a cluster sample. The results showed that adolescents response when following the game in HIVrelated health promotion activities and drug stated that the activities was very useful (99,3%), were satisfied with the activity (97,3%), this kind of activity is very attractive (99,3%), is very appropriate edutainment activities for adolescents and 87,8% said the material more easily understood. Therefore, developing method of health promotion on HIV / AIDS and drugs through the game of snakes and ladders is necessary.